Comparative analysis of Internet service providers' competition and Internet usage pattern. - Seow, Shin Horng. (2008)
Our study is divided into two parts. In the first study, we try to evalute three of the major Internet Services Providers (ISPs) in Singapore, based on their pricing, Quality of Services (QoS), value-added services, versioning, advertising and loyalty programs. Our objective is to find out which of the three ISPs' Internet access options is the most attractive to most of the consumers.In our second study, we looked into the usage of the Internet by Nanyang Tachnological University's undergraduates. Questions like the reasons for selecting certain ISP and the ISP user churn: rate, direction and reasons are covered. In addition, we also did four comparative studies based on male verse female, School of Accountancy and Business (SAB) versus Engineering faculy, nationals versus non-nationals and novice versus intermediate Internet users.